Characterization of Inhaled Nitric Oxide Use for Cardiac Indications in Pediatric Patients*. Issue 4 (23rd February 2022) - Yates, Andrew R.; Berger, John T.; Reeder, Ron W.; Banks, Russell; Mourani, Peter M.; Berg, Robert A.; Carcillo, Joseph A.; Carpenter, Todd; Hall, Mark W.; Meert, Kathleen L.; McQuillen, Patrick S.; Pollack, Murray M.; et al.
Abstract : OBJECTIVES: Characterize the use of inhaled nitric oxide (iNO) for pediatric cardiac patients and assess the relationship between patient characteristics before iNO initiation and outcomes following cardiac surgery. DESIGN: Observational cohort study. SETTING: PICU and cardiac ICUs in seven Collaborative Pediatric Critical Care Research Network hospitals. PATIENTS: Consecutive patients, less than 18 years old, mechanically ventilated before or within 24 hours of iNO initiation. iNO was started for a cardiac indication and excluded newborns with congenital diaphragmatic hernia, meconium aspiration syndrome, and persistent pulmonary hypertension, or when iNO started at an outside institution. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Four-hundred seven patients with iNO initiation based on cardiac dysfunction. Cardiac dysfunction patients were administered iNO for a median of 4 days (2–7 d). There was significant morbidity with 51 of 407 (13%) requiring extracorporeal membrane oxygenation and 27 of 407 (7%) requiring renal replacement therapy after iNO initiation, and a 28-day mortality of 46 of 407 (11%). Of the 366 (90%) survivors, 64 of 366 patients (17%) had new morbidity as assessed by Functional Status Scale. Among the postoperative cardiac surgical group ( n = 301), 37 of 301 (12%) had a superior cavopulmonary connection and nine of 301 (3%) had a Fontan procedure. Based on echocardiographic variables prior to iNO ( n = 160) in the postoperative surgical group, right ventricle dysfunction was associated with 28-day and hospital mortalities (both, p < 0.001) and ventilator-free days ( p = 0.003); tricuspid valve regurgitation was only associated with ventilator-free days ( p < 0.001), whereas pulmonary hypertension was not associated with mortality or ventilator-free days. CONCLUSIONS: Pediatric patients in whom iNO was initiated for a cardiac indication had a high mortality rate and significant morbidity. Right ventricular dysfunction, but not the presence of pulmonary hypertension on echocardiogram, was associated with ventilator-free days and mortality.